Green synthesis of bisphenol F over 12-phosphotungstic acid supported on acid-activated palygorskite1. Issue 77 (22nd August 2015) - Liu, Ran; Niu, Xiaozhen; Xia, Xinnian; Zeng, Zebing; Zhang, Guozhong; Lu, Yanbing
<x xml:space="preserve">Abstract</x> Hydroxyalkylation of phenol to bisphenol F under mild conditions over various solid acid catalysts.